PROSPECTS FOR THE DEVELOPMENT OF THE STATE ECONOMY BY INCREASING THE FINANCIAL LITERACY OF THE POPULATION (American Journal of Interdisciplinary Research and Development, 2023)
The article analyzes the international and Uzbekistan experience of introducing financial literacy of the population at the state level and with the involvement of banking organizations and educational institutions, describes the current state of the issue under study. The National Program for Improving the Level of Financial Literacy of the Population of the Uzbekistan is presented in the article as a document that will formulate the goals and objectives of the state policy aimed at increasing the level of financial literacy of the population of the Uzbekistan, which will contain the mechanisms for implementing such a policy, the principles for distributing the powers of all parties involved, as well as specific initiatives and measures to achieve the goals. The article also puts forward proposals to improve the financial literacy of the population for various categories of citizens: for teachers, partner organizations, the population - users of Internet resources, older people studying in various educational institutions in the form of classical types of education (in classrooms). The article proposes to create experimental sites - financial literacy clubs to improve the financial literacy of students in grades 5-9 of secondary schools in the Uzbekistan.